Affects et dimensions collectives dans l’activité d’ajustement lors d’épisodes d’improvisation - Pierre-Alain Filippi; Frédéric Saujat (Éducation et Socialisation)
Since the end of IUFM, the masterisation (2010), the ESPE (2014) and the INSPE (2019) have followed. These reforms in initial teacher training have greatly transformed the work of professionals in these settings. Beyond the structural changes, this article focuses on the work of trainers from the fine grain of their activity within the systems prescribed by the reforms. More precisely, it’s from an improvised episode where an experienced trainer, affected by an exchange between beginner peers, tried to interrupt a training situation that we highlight conflicts in her adjustment activity caused by the unaccompanied introduction of new devices. We will also show how an intervention-research mechanism enabled a collective of trainers to revisit this situation, to analyze it and to engage in a potential development of their adjustment activity and to draw potential avenues of transformation of their activity.